2010
DOI: 10.1159/000317910
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless Vitrectomy

Abstract: The introduction of pars plana vitrectomy was a revolution in ophthalmic surgery which allowed successful treatment of many previously untreatable conditions. After rapid early technical development, 3-port 20-gauge vitrectomy became established as the norm. Recent years have seen the introduction of new and innovative systems for performing vitrectomy without the need for sutures. This article describes the history of sutureless vitrectomy, and reviews the literature addressing the advantages and disadvantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…One important factor is inadequate wound closure in sutureless PPV surgeries due to a propensity for wound leak and subsequent intraocular ingress of surface microorganisms. [13][14][15][16] Compared with sutured PPV, a relatively higher risk of endophthalmitis in sutureless PPV has been previously reported. [17][18][19] However, later studies have demonstrated no significant difference in endophthalmitis in the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…One important factor is inadequate wound closure in sutureless PPV surgeries due to a propensity for wound leak and subsequent intraocular ingress of surface microorganisms. [13][14][15][16] Compared with sutured PPV, a relatively higher risk of endophthalmitis in sutureless PPV has been previously reported. [17][18][19] However, later studies have demonstrated no significant difference in endophthalmitis in the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although most large clinical trials have so far been focused on CNV related to AMD, some studies have demonstrated the satisfactory efficiency of anti-VEGF agents on CNV secondary to other causes [20,21,22,23,24], such as pathologic myopia [25,26]. Tachyphylaxis is defined as a decreasing therapeutic response to a pharmacological agent following repeated administration over time but excluding other unfavorable responses such as a tear in the retinal pigment epithelium and, therefore, a decrease in vision during treatment.…”
Section: Therapeutic Strategymentioning
confidence: 99%
“…Theoretical concerns that TSV could predispose to endophthalmitis are highlighted in Table 4 [48]. Laboratory studies on human cadaveric eyes and rabbit eyes have demonstrated that sutured 20-gauge sclerotomies are the most secure, and that sutureless sclerotomy leakage for 23-and 25-gauge can be minimized by angled (oblique) incision rather than straight incision [49][50][51].…”
Section: Endophthalmitis Following Vitrectomy: Risk Factorsmentioning
confidence: 99%
“…Intraoperatively, it remains crucial to assess wound integrity, and if any doubt of wound leak is present then the sclerotomy should be sutured. Moreover, the changing concept regarding the remnant vitreous skirt in sutureless smallgauge vitrectomy leading to vitreous incarceration in the wound can help in preventing hypotony but can potentially be a risk factor for infection [48].…”
Section: Endophthalmitis Following Vitrectomy: Risk Factorsmentioning
confidence: 99%